Cellulose nanofibril composite antibacterial decorative base paper and preparation method thereof

CN122649276BActive Publication Date: 2026-10-16ZHEJIANG FORESTRY UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611064465.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-17
Publication Date
2026-10-16
Estimated Expiration
2046-07-17

AI Technical Summary

Technical Problem

然而,钛白粉颗粒细小、比表面积大,在造纸湿部体系中易随白水流失,留着率低,不仅造成原料浪费,还会增加白水系统的污染负荷

Benefits of technology

1、本发明提供了一种纤维素纳米纤丝复合抑菌装饰原纸,该装饰原纸兼具优异的抑菌防霉性能、湿抗张强度、钛白粉留着率和透气度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
  • Figure SMS_4
    Figure SMS_4
Patent Text Reader

Abstract

The present application relates to the technical field of papermaking, and particularly relates to a cellulose nanofibril composite bacteriostatic decorative base paper and a preparation method thereof. The decorative base paper is composed of the following raw materials: mixed pulp, composite filler and papermaking additive; the mass ratio of the mixed pulp, the composite filler and the papermaking additive is 1:(0.5-0.55):(0.02-0.05); the papermaking additive is composed of cationic cellulose nanofibril, anionic cellulose nanofibril, creatine and modified polyamide polyamine epichlorohydrin with a mass ratio of 1:(0.5-2):(0.1-0.3):(0.3-1). The decorative base paper has excellent bacteriostatic and mildew-proof performance, wet tensile strength, titanium dioxide retention rate and air permeability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of papermaking technology, and in particular to a cellulose nanofiber composite antibacterial decorative base paper and its preparation method. Background Technology

[0002] Decorative base paper is a specialty industrial paper produced using high-quality wood pulp and titanium dioxide as main raw materials through a special process. It is primarily used as a surface material for engineered wood products such as fiberboard and particleboard. In recent years, decorative base paper has been widely used in home decoration, renovation, and wooden furniture, with market demand continuing to grow.

[0003] The addition of titanium dioxide imparts excellent whiteness and gloss to paper, resulting in a smooth and fine surface with good printability. However, titanium dioxide particles are small and have a large specific surface area, making them prone to loss with white water in the wet end of papermaking systems, resulting in low retention. This not only wastes raw materials but also increases the pollution load on the white water system. Simultaneously, decorative base paper is susceptible to moisture and mold growth during storage and use, affecting the finish quality and service life. All of these problems are closely related to the performance of papermaking additives. Therefore, developing a papermaking additive system that can simultaneously improve titanium dioxide retention and paper's antibacterial and antifungal properties has significant practical application value. Summary of the Invention

[0004] In order to overcome the shortcomings of the prior art, one of the objectives of the present invention is to provide a cellulose nanofiber composite antibacterial decorative base paper, which has excellent antibacterial and antifungal properties, wet tensile strength, titanium dioxide retention rate and air permeability.

[0005] The second objective of this invention is to provide a method for preparing cellulose nanofiber composite antibacterial decorative base paper. This preparation method is simple, controllable, and suitable for industrial production.

[0006] One of the objectives of this invention is achieved through the following technical solution: A cellulose nanofiber composite antibacterial decorative base paper is composed of the following raw materials: mixed pulp, composite filler, and papermaking additives; the mass ratio of the mixed pulp, composite filler, and papermaking additives is 1:(0.5-0.55):(0.02-0.05); the papermaking additives are composed of cationic cellulose nanofibers, anionic cellulose nanofibers, creatine, and modified polyamide polyamine epichlorohydrin in a mass ratio of 1:(0.5-2):(0.1-0.3):(0.3-1). The preparation process of the modified polyamide polyamine epichlorohydrin is as follows: Under the action of a catalyst, organic amines and diacids undergo a polycondensation reaction to obtain polyamide polyamine prepolymers; epichlorohydrin is added to the polyamide polyamine prepolymers to continue the reaction, thus obtaining the final product.

[0007] The modification principle of the modified polyamide polyamine epichlorohydrin of this invention is as follows: In the synthesis stage of polyamide polyamine prepolymer, modified succinic acid is partially substituted for succinic acid and subjected to a polycondensation reaction with organic amines to introduce the phenyltriazole structure and additional quaternary ammonium cation sites into the prepolymer molecular chain; the resulting prepolymer is further reacted with epichlorohydrin to finally obtain modified polyamide polyamine epichlorohydrin.

[0008] Preferably, the solid content of the polyamide polyamine prepolymer is 40-50%; the solid content of the modified polyamide polyamine epichlorohydrin is 15-20%, and the pH is 5-6.

[0009] Preferably, the molar ratio of the diacid, organic amine, catalyst, and epichlorohydrin is 1:(0.95-1.05):(0.03-0.06):(0.4-0.6); the diacid is composed of modified succinic acid and succinic acid in a molar ratio of 1:(4-8). The structural formula of the modified succinic acid is: .

[0010] Preferably, the preparation process of the modified succinic acid is as follows: (a) Benzonitrile, 1,1-dimethylguanidine hydrochloride, cesium carbonate, and cuprous bromide were added to dimethyl sulfoxide, stirred and reacted, and then purified to obtain intermediate 1; The structural formula of intermediate 1 is: (b) 2,3-Dibromosuccinic acid was added to methanol, the pH was adjusted, intermediate 1 was added, the reaction was stirred and then purified to obtain the modified succinic acid.

[0011] The preparation principle of the modified succinic acid of this invention is as follows: First, benzonitrile and 1,1-dimethylguanidine hydrochloride were used as raw materials to prepare intermediate 1 containing a phenyltriazole structure via a cyclization condensation reaction. Subsequently, the tertiary amine nitrogen in intermediate 1 underwent a quaternization reaction with 2,3-dibromosuccinic acid to obtain modified succinic acid.

[0012] Preferably, the molar ratio of benzonitrile, 1,1-dimethylguanidine hydrochloride, cesium carbonate, and cuprous bromide in step (a) is 1:(1.5-1.6):(3-3.1):(0.05-0.06); the stirring reaction is carried out at a temperature of 120-125°C for 24-26 hours.

[0013] Preferably, in step (b), the molar ratio of 2,3-dibromosuccinic acid to intermediate 1 is 1:(2.2-2.4); the stirring reaction temperature is 30-35°C, and the time is 24-28h; the pH is adjusted to 9-9.2.

[0014] Preferably, the catalyst is selected from p-toluenesulfonic acid, sulfuric acid, and dodecylbenzenesulfonic acid; the organic amine is selected from diethylenetriamine, triethylenetetramine, and tetraethylenepentamine.

[0015] Preferably, the polycondensation reaction is carried out at a temperature of 120-150°C for 2-4 hours; the continued reaction includes: first reacting at 22-24°C for 0.5-3 hours, and then raising the temperature to 45-60°C for 1-3 hours.

[0016] Preferably, the composite filler is composed of titanium dioxide and talc in a mass ratio of 1:(0.15-0.3); the mixed pulp is composed of softwood pulp, hardwood pulp and waste pulp in a mass ratio of 1:(0.65-0.75):(0.05-0.1); the concentration of the mixed pulp is 3-5wt%, and the freeness is 25-30°SR.

[0017] Preferably, the anionic cellulose nanofibers are phosphorylated cellulose nanofibers; the cationic cellulose nanofibers are quaternized ammonium salt cellulose nanofibers.

[0018] The second objective of this invention is achieved by the following technical solution: The preparation method of the above-mentioned cellulose nanofiber composite antibacterial decorative base paper includes the following steps: The composite filler and cationic cellulose nanofibers are dispersed in water to prepare a dispersion with a solid content of 12-15%. Mixed pulp and anionic cellulose nanofibers are added, followed by creatine and modified polyamide polyamine epichlorohydrin. The mixture is then processed through wire forming, pressing, and drying.

[0019] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. This invention provides a cellulose nanofiber composite antibacterial decorative base paper, which has excellent antibacterial and antifungal properties, wet tensile strength, titanium dioxide retention rate and air permeability.

[0020] 2. This invention improves the antibacterial and antifungal properties, as well as the wet tensile strength, of decorative base paper by adding modified polyamide polyamine epichlorohydrin obtained through a specific modification method to papermaking additives. Specifically, through modified succinic acid copolymerization, a phenyltriazole structure and additional quaternary ammonium cation sites are introduced into the modified polyamide polyamine epichlorohydrin. The synergistic effect of these two components not only enhances the wet strength of the paper but also forms a dual antibacterial system, endowing the paper with antibacterial and antifungal properties.

[0021] 3. This invention improves the titanium dioxide retention rate of decorative base paper by adding creatine to papermaking additives. Specifically, anionic and cationic cellulose nanofibers in the papermaking additives can form a flocculent structure, improving the titanium dioxide retention rate. Creatine is electrically neutral at the pulp pH but carries both positive and negative charge regions. It can interact with anionic fibers or fibers through its positively charged region and with cationic fibers through its negatively charged region, acting as a "charge buffer" and "dispersion stabilizer," preventing excessive flocculation of nanofibers and thus optimizing the retention effect. At the same time, the addition of anionic and cationic cellulose nanofibers improves the wet tensile strength of the paper while maintaining its original high air permeability.

[0022] 4. The present invention also provides a method for preparing cellulose nanofiber composite antibacterial decorative base paper. The preparation method is simple, controllable, and suitable for industrial production. Detailed Implementation

[0023] The present invention will now be further described in conjunction with specific embodiments. It should be noted that, without conflict, the various embodiments or technical features described below can be arbitrarily combined to form new embodiments. Specific conditions not specified in the embodiments shall be performed according to conventional conditions or conditions recommended by the manufacturer. Unless otherwise specified, all reagents or instruments used are conventional products obtained through commercial channels.

[0024] In this invention, the anionic cellulose nanofibers are phosphorylated cellulose nanofibers, and the cationic cellulose nanofibers are quaternized ammonium salt cellulose nanofibers.

[0025] Preparation Example 1 The preparation process of modified succinic acid is as follows: (a) Benzonitrile, 1,1-dimethylguanidine hydrochloride, cesium carbonate, cuprous bromide, and dimethyl sulfoxide were added sequentially to a reaction flask in a ratio of 0.3 mol: 0.46 mol: 0.92 mol: 0.017 mol: 1.2 mL. After mixing thoroughly, the mixture was sealed and stirred at 123 °C under normal atmospheric pressure for 25 h. After the reaction was completed, the mixture was cooled to room temperature, diluted with ethyl acetate, and washed sequentially with 5 wt% sodium bicarbonate aqueous solution and saturated saline solution. The organic phase was dried over anhydrous magnesium sulfate, and the solvent was removed by concentration under reduced pressure. The crude product was purified by column chromatography (V... 己烷 V 乙酸乙酯 =1:4), intermediate 1 was obtained; the NMR and mass spectrometry results of intermediate 1 are as follows: 1 HNMR: (C10 H 12 N4, 400MHz, DMSO-d6) δ: 3.06 (s, 6H), 7.42-7.52 (m, 3H), 8.05-8.09 (dd, 2H), 9.61 (s, 1H). MS (ESI) m / z=188.11 [M].

[0026] (b) Using 2,3-dibromosuccinic acid, intermediate 1, and methanol in a ratio of 10 mmol: 23 mmol: 70 mL, 2,3-dibromosuccinic acid was dissolved in methanol. The pH of the solution was adjusted to 9.1 with 20 wt% ammonia solution. Then, intermediate 1 was added, and the mixture was stirred at 34 °C for 26 h. After the reaction was complete, the methanol was evaporated to dryness, and the residue was redissolved in deionized water. The pH was adjusted to 2.5 by adding 1 mol / L hydrochloric acid solution to precipitate the product. The solid product was collected by filtration, washed with cold water, and purified by column chromatography (V... 正丙醇 V 水 =8:1), to obtain modified succinic acid; the NMR and mass spectrometry results of the modified succinic acid are as follows: 1 HNMR: (C 24 H 28 O4N8 2+ , 400MHz, DMSO-d6) δ: 2.90 (s, 12H), 5.39 (s, 2H), 7.42-7.52 (m, 6H), 8.05-8.09 (dd, 4H), 12.92 (s, 2H), 13.72 (s, 2H). MS (ESI) m / z=246.11 [M / 2].

[0027] Preparation Example 2 The preparation process of modified succinic acid is as follows: (a) Benzonitrile, 1,1-dimethylguanidine hydrochloride, cesium carbonate, cuprous bromide, and dimethyl sulfoxide were added sequentially to a reaction flask at a ratio of 0.3 mol: 0.45 mol: 0.9 mol: 0.015 mol: 1 mL. The mixture was then sealed and stirred at 120 °C under normal atmospheric pressure for 26 h. After the reaction was completed, the mixture was cooled to room temperature. The reaction solution was diluted with ethyl acetate and washed sequentially with 5 wt% sodium bicarbonate aqueous solution and saturated saline solution. The organic phase was dried over anhydrous magnesium sulfate and concentrated under reduced pressure to remove the solvent. The crude product was purified by column chromatography (V... 己烷 V 乙酸乙酯 =1:4), to obtain intermediate 1; the NMR and mass spectrometry results of intermediate 1 are consistent with those of preparation example 1.

[0028] (b) Using 2,3-dibromosuccinic acid, intermediate 1, and methanol in a ratio of 10 mmol: 22 mmol: 60 mL, 2,3-dibromosuccinic acid was dissolved in methanol. The pH of the solution was adjusted to 9 with 20 wt% ammonia solution. Then, intermediate 1 was added, and the mixture was stirred at 30 °C for 28 h. After the reaction was complete, the methanol was evaporated to dryness, and the residue was redissolved in deionized water. The pH was adjusted to 2 by adding 1 mol / L hydrochloric acid solution to precipitate the product. The solid product was collected by filtration, washed with cold water, and purified by column chromatography (V... 正丙醇 V 水 =8:1), to obtain modified succinic acid; the NMR and mass spectrometry results of the modified succinic acid were consistent with those of Preparation Example 1.

[0029] Preparation Example 3 The preparation process of modified succinic acid is as follows: (a) Benzonitrile, 1,1-dimethylguanidine hydrochloride, cesium carbonate, cuprous bromide, and dimethyl sulfoxide were added sequentially to a reaction flask in a ratio of 0.3 mol: 0.48 mol: 0.93 mol: 0.018 mol: 1.5 mL. After mixing thoroughly, the mixture was sealed and stirred at 125 °C under normal atmospheric pressure for 24 h. After the reaction was completed, the mixture was cooled to room temperature, diluted with ethyl acetate, and washed sequentially with 5 wt% sodium bicarbonate aqueous solution and saturated saline solution. The organic phase was dried over anhydrous magnesium sulfate, and the solvent was removed by concentration under reduced pressure. The crude product was purified by column chromatography (V... 己烷 V 乙酸乙酯 =1:4), to obtain intermediate 1; the NMR and mass spectrometry results of intermediate 1 are consistent with those of preparation example 1.

[0030] (b) Using 2,3-dibromosuccinic acid, intermediate 1, and methanol in a ratio of 10 mmol:24 mmol:80 mL, 2,3-dibromosuccinic acid was dissolved in methanol. The pH of the solution was adjusted to 9.2 with 20 wt% ammonia solution. Then, intermediate 1 was added, and the mixture was stirred at 35 °C for 24 h. After the reaction was complete, the methanol was evaporated to dryness, and the residue was redissolved in deionized water. The pH was adjusted to 3 by adding 1 mol / L hydrochloric acid solution to precipitate the product. The solid product was collected by filtration, washed with cold water, and purified by column chromatography (V... 正丙醇 V 水 =8:1), to obtain modified succinic acid; the NMR and mass spectrometry results of the modified succinic acid were consistent with those of Preparation Example 1.

[0031] Preparation Example 4 The preparation process of modified polyamide polyamine epichlorohydrin is as follows: With a molar ratio of diacid, diethylenetriamine, p-toluenesulfonic acid, and epichlorohydrin of 1:1:0.05:0.5, diethylenetriamine and diacid were reacted at 140°C for 3 hours under the action of p-toluenesulfonic acid. After dilution with water, a polyamide polyamine prepolymer with a solid content of 44% was obtained. The diacid was composed of modified succinic acid and succinic acid from Preparation Example 1 in a molar ratio of 1:7. Epichlorohydrin was added dropwise to the above polyamide polyamine prepolymer. After the addition was completed, the reaction was carried out at 23°C for 2 hours, and then the temperature was raised to 50°C and the reaction was continued for 2 hours. Formic acid was added to terminate the reaction, and the mixture was diluted with water to obtain modified polyamide polyamine epichlorohydrin with a solid content of 18% and a pH of 5.4.

[0032] Preparation Example 5 The preparation process of modified polyamide polyamine epichlorohydrin is as follows: With a molar ratio of diacid, triethylenetetramine, sulfuric acid, and epichlorohydrin of 1:0.95:0.03:0.4, triethylenetetramine and diacid were reacted at 120°C for 4 hours under the action of sulfuric acid. After dilution with water, a polyamide polyamine prepolymer with a solid content of 40% was obtained. The diacid was composed of modified succinic acid and succinic acid from Preparation Example 2 in a molar ratio of 1:4. Epichlorohydrin was added dropwise to the above polyamide polyamine prepolymer. After the addition was completed, the reaction was carried out at 24°C for 0.5 hours. Then, the temperature was raised to 45°C and the reaction was continued for 3 hours. Formic acid was added to terminate the reaction. After dilution with water, a modified polyamide polyamine epichlorohydrin with a solid content of 15% and a pH of 5 was obtained.

[0033] Preparation Example 6 The preparation process of modified polyamide polyamine epichlorohydrin is as follows: With a molar ratio of 1:1.05:0.06:0.6 for dicarboxylic acid, tetraethylenepentamine, dodecylbenzenesulfonic acid, and epichlorohydrin, tetraethylenepentamine and dicarboxylic acid were reacted at 150°C for 2 hours under the action of dodecylbenzenesulfonic acid. After dilution with water, a polyamide polyamine prepolymer with a solid content of 50% was obtained. The dicarboxylic acid was composed of modified succinic acid and succinic acid in Preparation Example 3 at a molar ratio of 1:8. Epichlorohydrin was added dropwise to the above polyamide polyamine prepolymer. After the addition was completed, the reaction was carried out at 22°C for 3 hours. Then, the temperature was raised to 60°C and the reaction was continued for 1 hour. Formic acid was added to terminate the reaction. After dilution with water, a modified polyamide polyamine epichlorohydrin with a solid content of 20% and a pH of 6 was obtained.

[0034] Preparation Example 7 The difference between this preparation example and preparation example 4 is that the modified succinic acid used in preparation example 4 is replaced with an equimolar amount of succinic acid, that is, all the dicarboxylic acids are succinic acid, and the amount used is the sum of the molar amounts of modified succinic acid and succinic acid in preparation example 4; the remaining steps and process conditions are the same as in preparation example 4.

[0035] Example 1 A cellulose nanofiber composite antibacterial decorative base paper is composed of the following raw materials: mixed pulp, composite filler, and papermaking additives. The mass ratio of the mixed pulp, composite filler, and papermaking additives is 1:0.52:0.04.

[0036] The above-mentioned papermaking additive is composed of cationic cellulose nanofibers, anionic cellulose nanofibers, creatine, and modified polyamide polyamine epichlorohydrin of Preparation Example 4 in a mass ratio of 1:1:0.2:0.7.

[0037] The composite filler is composed of titanium dioxide and talc in a mass ratio of 1:0.2; the mixed pulp is composed of softwood pulp, hardwood pulp and waste pulp in a mass ratio of 1:0.7:0.08, the concentration of the mixed pulp is 4wt%, and the freeness is 26°SR.

[0038] The preparation method of the above-mentioned cellulose nanofiber composite antibacterial decorative base paper includes the following steps: Composite fillers and cationic cellulose nanofibers are dispersed in water to prepare a dispersion with a solid content of 14%. Mixed pulp and anionic cellulose nanofibers are then added and mixed thoroughly. Creatine and modified polyamide polyamine epichlorohydrin are then added and mixed evenly. The mixture is subsequently subjected to wire forming, pressing, and drying processes. During the wire forming process, the paper basis weight is 80 g / m². 2 .

[0039] Example 2 A cellulose nanofiber composite antibacterial decorative base paper is composed of the following raw materials: mixed pulp, composite filler, and papermaking additives. The mass ratio of the mixed pulp, composite filler, and papermaking additives is 1:0.5:0.02.

[0040] The above-mentioned papermaking additive is composed of cationic cellulose nanofibers, anionic cellulose nanofibers, creatine, and modified polyamide polyamine epichlorohydrin of Preparation Example 5 in a mass ratio of 1:0.5:0.1:0.3.

[0041] The composite filler is composed of titanium dioxide and talc in a mass ratio of 1:0.15; the mixed pulp is composed of softwood pulp, hardwood pulp and waste pulp in a mass ratio of 1:0.65:0.05, the concentration of the mixed pulp is 3wt%, and the freeness is 25°SR.

[0042] The preparation method of the above-mentioned cellulose nanofiber composite antibacterial decorative base paper includes the following steps: Composite fillers and cationic cellulose nanofibers are dispersed in water to prepare a dispersion with a solid content of 12%. Mixed pulp and anionic cellulose nanofibers are then added and mixed thoroughly. Creatine and modified polyamide polyamine epichlorohydrin are then added and mixed evenly. The mixture is subsequently subjected to wire forming, pressing, and drying processes. During the wire forming process, the paper basis weight is 80 g / m². 2 .

[0043] Example 3 A cellulose nanofiber composite antibacterial decorative base paper is composed of the following raw materials: mixed pulp, composite filler, and papermaking additives. The mass ratio of the mixed pulp, composite filler, and papermaking additives is 1:0.55:0.05.

[0044] The above-mentioned papermaking additive is composed of cationic cellulose nanofibers, anionic cellulose nanofibers, creatine, and modified polyamide polyamine epichlorohydrin of Preparation Example 6 in a mass ratio of 1:2:0.3:1.

[0045] The composite filler is composed of titanium dioxide and talc in a mass ratio of 1:0.3; the mixed pulp is composed of softwood pulp, hardwood pulp and waste pulp in a mass ratio of 1:0.75:0.1, the concentration of the mixed pulp is 5wt%, and the freeness is 30°SR.

[0046] The preparation method of the above-mentioned cellulose nanofiber composite antibacterial decorative base paper includes the following steps: Composite fillers and cationic cellulose nanofibers are dispersed in water to prepare a dispersion with a solid content of 15%. Mixed pulp and anionic cellulose nanofibers are then added and mixed thoroughly. Creatine and modified polyamide polyamine epichlorohydrin are then added and mixed evenly. The mixture is subsequently subjected to wire forming, pressing, and drying processes. During the wire forming process, the paper basis weight is 80 g / m². 2 .

[0047] Comparative Example 1 The difference between this comparative example and Example 1 is that the polyamide polyamine epichlorohydrin of Preparation Example 7 was used instead of the modified polyamide polyamine epichlorohydrin of Preparation Example 4.

[0048] Comparative Example 2 The difference between this comparative example and Example 1 is that creatine was not added to the papermaking additives.

[0049] Experimental Example 1 Antimicrobial tests were conducted in accordance with GB / T 42702-2023. The tested bacteria were Staphylococcus aureus, Escherichia coli, and Candida albicans. The results are shown in Table 1.

[0050] The anti-mold performance was tested according to GB / T 24346-2009, using Aspergillus niger as the test strain. The results are shown in Table 1. The anti-mold rating standards are as follows: Level 0: No mold growth; Level 1: Small amount of mold growth, accounting for less than 10% of the total area; Level 2: Relatively large amount of mold growth, accounting for 10%-30% of the total area; Level 3: Very large amount of mold growth, accounting for 30%-60% of the total area; Level 4: Very serious mold growth, accounting for more than 60% of the total area.

[0051] Table 1 As shown in Table 1, the decorative base paper prepared in Examples 1-3 of this invention exhibits an antibacterial rate of over 96% against Staphylococcus aureus, Escherichia coli, and Candida albicans, with a mildew resistance level of 0, demonstrating excellent antibacterial and mildew-resistant properties. Comparative Example 1, using ordinary PAE (polyamide polyamine epichlorohydrin) without modified succinic acid copolymerization, shows a significant decrease in antibacterial rate to 54.6%-63.5% and a mildew resistance level of 2. This indicates that the phenyltriazole structure and additional quaternary ammonium cation sites introduced into the PAE molecule by the modified succinic acid copolymerization can synergistically form a dual antibacterial system with the inherent quaternary ammonium salt groups of PAE, significantly improving the antibacterial and mildew-resistant properties of the paper. Comparative Example 2, without the addition of creatine, has an antibacterial rate and mildew resistance level essentially equivalent to Example 1, indicating that creatine has no direct impact on antibacterial and mildew-resistant properties. In summary, this invention successfully endows decorative base paper with excellent antibacterial and mildew-resistant properties through modified succinic acid copolymerization of PAE.

[0052] Experimental Example 2 Wet tensile strength: Tested according to GB / T 465.2-2008, and the results are shown in Table 2.

[0053] Titanium dioxide retention rate: The base paper obtained in the examples or comparative examples was dried at 102°C for 20 min and then weighed. It was then placed in a crucible and incinerated in a muffle furnace under the following conditions: 100°C for 5 min; 200°C for 10 min; 540°C for 5 h. After incineration, the paper was removed, dried, and weighed. The titanium dioxide retention rate was calculated using the following formula: N = m / [(1-a) × A] × 100%; where N is the titanium dioxide retention rate, %; m is the mass after incineration, g; A is the mass of composite filler added to the base paper, g; a is the mass loss rate of filler during incineration, a is 0.89%, and the results are shown in Table 2.

[0054] Air permeability: Tested using a Gurley-4110N air permeability tester, with a sample size of 100cm. 2 The results for the circular paper pieces are shown in Table 2.

[0055] Table 2 As shown in Table 2, the decorative base paper prepared in Examples 1-3 of this invention possesses excellent wet tensile strength, titanium dioxide retention rate, and air permeability. The wet strength is above 12.5 N / 15 mm, and the retention rate is above 86.4%. Comparative Example 1, using unmodified ordinary PAE, showed a decrease in wet tensile strength to 6.4 N / 15 mm, indicating that the phenyltriazole structure introduced by the modified succinic acid copolymerization provides additional hydrogen bond crosslinking sites, significantly enhancing the wet bonding force between fibers. Comparative Example 2, without creatine, showed a wet tensile strength essentially the same as Example 1, but a significantly reduced titanium dioxide retention rate. This indicates that creatine plays a "charge buffering" and "dispersion stabilizing" role in the system, effectively preventing excessive flocculation of anionic and cationic nanofibers and forming a uniform network structure to encapsulate and retain titanium dioxide particles. Simultaneously, the addition of anionic and cationic cellulose nanofibers improved the paper's wet tensile strength while maintaining its original high air permeability. In summary, this invention achieves a simultaneous improvement in the wet strength and filler retention of decorative base paper by combining modified PAE with creatine.

[0056] The above embodiments are merely preferred embodiments of the present invention and should not be construed as limiting the scope of protection of the present invention. Any non-substantial changes and substitutions made by those skilled in the art based on the present invention shall fall within the scope of protection claimed by the present invention.

Claims

1. A cellulose nanofiber composite antibacterial decorative base paper, characterized in that, It is composed of the following raw materials: mixed pulp, composite filler, and papermaking additives; the mass ratio of the mixed pulp, composite filler, and papermaking additives is 1:(0.5-0.55):(0.02-0.05); the papermaking additives are composed of cationic cellulose nanofibers, anionic cellulose nanofibers, creatine, and modified polyamide polyamine epichlorohydrin in a mass ratio of 1:(0.5-2):(0.1-0.3):(0.3-1). The preparation process of the modified polyamide polyamine epichlorohydrin is as follows: Under the action of a catalyst, organic amines and diacids undergo a polycondensation reaction to obtain a polyamide polyamine prepolymer; epichlorohydrin is added to the polyamide polyamine prepolymer to continue the reaction, thus obtaining the final product. The dicarboxylic acid is composed of modified succinic acid and succinic acid in a molar ratio of 1:(4-8); The structural formula of the modified succinic acid is: 。 2. The cellulose nanofiber composite antibacterial decorative base paper according to claim 1, characterized in that, The molar ratio of the dicarboxylic acid, organic amine, catalyst, and epichlorohydrin is 1:(0.95-1.05):(0.03-0.06):(0.4-0.6).

3. The cellulose nanofiber composite antibacterial decorative base paper according to claim 2, characterized in that, The preparation process of the modified succinic acid is as follows: (a) Benzonitrile, 1,1-dimethylguanidine hydrochloride, cesium carbonate, and cuprous bromide were added to dimethyl sulfoxide, stirred and reacted, and then purified to obtain intermediate 1; The structural formula of intermediate 1 is: (b) 2,3-Dibromosuccinic acid was added to methanol, the pH was adjusted, intermediate 1 was added, the reaction was stirred and then purified to obtain the modified succinic acid.

4. The cellulose nanofiber composite antibacterial decorative base paper according to claim 3, characterized in that, In step (a), the molar ratio of benzonitrile, 1,1-dimethylguanidine hydrochloride, cesium carbonate, and cuprous bromide is 1:(1.5-1.6):(3-3.1):(0.05-0.06); the stirring reaction is carried out at a temperature of 120-125°C for 24-26 hours.

5. The cellulose nanofiber composite antibacterial decorative base paper according to claim 3, characterized in that, In step (b), the molar ratio of 2,3-dibromosuccinic acid to intermediate 1 is 1:(2.2-2.4); the stirring reaction temperature is 30-35℃ and the time is 24-28h; the pH is adjusted to 9-9.

2.

6. The cellulose nanofiber composite antibacterial decorative base paper according to claim 2, characterized in that, The catalyst is selected from p-toluenesulfonic acid, sulfuric acid, and dodecylbenzenesulfonic acid; the organic amine is selected from diethylenetriamine, triethylenetetramine, and tetraethylenepentamine.

7. The cellulose nanofiber composite antibacterial decorative base paper according to claim 1, characterized in that, The polycondensation reaction is carried out at a temperature of 120-150℃ for 2-4 hours; the continued reaction includes: first reacting at 22-24℃ for 0.5-3 hours, and then raising the temperature to 45-60℃ for 1-3 hours.

8. The cellulose nanofiber composite antibacterial decorative base paper according to claim 1, characterized in that, The composite filler is composed of titanium dioxide and talc in a mass ratio of 1:(0.15-0.3); the mixed pulp is composed of softwood pulp, hardwood pulp, and waste pulp in a mass ratio of 1:(0.65-0.75):(0.05-0.1); the mixed pulp has a concentration of 3-5 wt% and a freeness of 25-30. ° SR.

9. The cellulose nanofiber composite antibacterial decorative base paper according to claim 1, characterized in that, The anionic cellulose nanofibers are phosphorylated cellulose nanofibers; the cationic cellulose nanofibers are quaternized ammonium salt cellulose nanofibers.

10. A method for preparing a cellulose nanofiber composite antibacterial decorative base paper according to any one of claims 1-9, characterized in that, Includes the following steps: The composite filler and cationic cellulose nanofibers are dispersed in water to prepare a dispersion with a solid content of 12-15%. Mixed pulp and anionic cellulose nanofibers are added, followed by creatine and modified polyamide polyamine epichlorohydrin. The mixture is then processed through wire forming, pressing, and drying.

Citation Information

Patent Citations

  • Wet-strength waste paper pulping method

    CN103835174A

  • Bio-based lubricating grease based on phosphorylated cellulose nanofibrils and preparation method of bio-based lubricating grease

    CN121495625A